Strategi Pengelolaan Media Sosial Instagram @disparbudpora_bondowoso sebagai Media Komunikasi dalam Mempromosikan Wisata Kabupaten Bondowoso - Malaihollo, Trifena Putri (Jurnal Ground Handling, 2024)
This research is motivated by the concern of the Bondowoso Regency Government which is less concerned about Banyumas Regency in promoting one of its leading tourist attractions, namely the Ijen Crater. The Ijen Crater has been designated as part of the World Geopark. Currently, many local and foreign tourists make the Ijen Crater a tourist destination in Banyumas because it is located in two regions. The purpose of this study was first to determine the management of social media by the @disparbudpora_bondowoso account, and second to determine the impact and results of social media management in promoting tourism in Bondowoso Regency. This study uses a qualitative method. Data were collected using observation techniques, direct interviews, and documentation. The conclusion that can be drawn is that the tourism promotion strategy implemented by the Disparbudpora is quite good in providing informative and interesting content, but there are obstacles in conducting evaluations, namely that it is not optimal. The impact of the management of the Bondowoso Disparbudpora social media in promoting tourism in Bondowoso Regency can be seen from the response of followers in the comments column, likes, and the reach achieved by the @disparbudpora_bondowoso Instagram account. The result of social media management by Disparbudpora is that its followers obtain relevant and quality information.